The adoption of IEC 62305 standards for lightning protection system in Malaysia: a success story - Ab Kadir, Mohd Zainal Abidin; Siow, Chun Lim; Jasni, Jasronita; Gomes, Chandima; Muluk, Iffah Hannah (IEEE, 2023)
This manuscript provides an overview of the adoption of the IEC 62305 standards for lightning protection systems (LPS) in Malaysia. It outlines the need for LPS in Malaysia by providing general lightning statistics, historical changes and adoption in LPS standards. For the first time, the manuscript explains the key reasons for the success of this transition of IEC 62305, which is now being regulated by the Energy Commission of Malaysia (EC). As the Regulator for energy and gas in Malaysia, EC has successfully transformed the standards into regulations by issuing the Directive paper in 2020, taking a big leap from its initial release as a Circular in 2011. Finally, it highlights the way forward in creating a culture of self-regulation among industrial players in Malaysia.